Rethinking Emergent Literacy in Children With Hearing Loss - Ingvalson, Erin M.; Grieco-Calub, Tina M.; Perry, Lynn K.; VanDam, Mark (Frontiers in Psychology, 2020)
Long-term literacy outcomes for children with hearing loss, particularly those with severe-to-profound deafness who are fitted with cochlear implants (CIs) lag behind those of children with normal hearing (NH). The causes for these long-term deficits are not fully clear, though differences in auditory access between children who use CIs and those with NH may be a partial cause. This paper briefly reviews the emergent literacy model as proposed by Whitehurst and Lonigan (1998). We then examine the development of each of Whitehurst and Lonigan’s identified factors in children who use CIs and how the extant knowledge of language and literacy development in children who use CIs may bear on the emergent literacy model. We then propose to modify the model for children who use CIs based on their unique developmental trajectories, influenced at least in part by their unique auditory access. We conclude with future directions for further development of an evidence-based emergent literacy model for children who use CIs and how this model could be used to inform intervention.